Effect of Massage Therapy on Transcutaneous Bilirubin Level in Healthy Term Neonates: Randomized Controlled Clinical Trial - Homa Babaei; Mazyar Vakiliamini (Mashhad University of Medical Sciences, 2018)
Background: Neonatal jaundice is a common condition in approximately 60% of term newborns during the first week after birth. Therefore, it is necessary to detect methods for the prevention of this problem.This study was conducted to evaluate the impact of massage therapy on transcutaneous bilirubin level in healthy term newborns. Methods: The present study was conducted on102 healthy term newborns. The newborns were randomly assigned to massage group and control group. The massage group received daily massage for five days from the first postnatal day while the control group received only routine neonatal care (without massage). In both groups, transcutaneous bilirubin level and frequency of defecation were the main studied variables. Results: The frequency of defecation in the massage group increased from 1.08 on the first day to 4.08 on the fifth day, whereas it increased from 0.865 on the first day to 2.731 on the fifth day in the control group, indicating a significant difference between the two groups (P